Implementation of the principles of the scientific concept “Medicine of borderline states” regarding donosological diagnosis and overcoming the risks of health deterioration in student youth - V.O. Korobchanskyi; V.V. Sarkis-Ivanova; O.S. Bohachova; Y.O. Oliinyk; S.V. Biеleсka (Medičnì Perspektivi)
Today, the methodological basis of disease prevention among various categories of the population, including students, is an innovative area of medical science and health care practice, namely medicine of borderline conditions. The development of a system of prenosological diagnosis of pathological conditions in young students and their hygienic correction for disease prevention are important both from a scientific and practical point of view. The study was conducted in the conditions of a natural experiment on the basis of three types of educational institutions, at the place of study of representatives of both sexes aged 14 to 23 years, adolescents and yound adults. In order to achieve the relevant objectives, the study used the following methods: analytic addressed at the study of educational programs, curricula, schedules, profile and regulatory documents; sanitary-hygienic; psychophysiological; psychological, statistic. Set of risk factors related to the educational process among young people studying in three types of educational institutions – secondary educational institutions, higher educational institution, Professional Agrarian Lyceum was analyzed. It is established that unfavorable living conditions affect donosological mental states of asthenic, hypochondriac and depressive nature.